2005
DOI: 10.1152/japplphysiol.00309.2005
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine improves endurance in 75-yr-old citizens: a randomized, double-blind, placebo-controlled, crossover study

Abstract: Norager, C. B., M. B. Jensen, M. R. Madsen, and S. Laurberg. Caffeine improves endurance in 75-yr-old citizens: a randomized, double-blind, placebo-controlled, crossover study. J Appl Physiol 99: 2302-2306, 2005. First published August 4, 2005 doi:10.1152/japplphysiol.00309.2005.-This study investigated the effect of caffeine on physical performance in healthy citizens aged Ն70 yr. The randomized, double-blind, placebo-controlled, crossover study was conducted in 15 men and 15 women recruited by their general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
82
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(96 citation statements)
references
References 38 publications
12
82
1
1
Order By: Relevance
“…The current results also agree with the prior research with younger adults (2) showing enhanced aerobic endurance following caffeine ingestion and research with older adults that has reported improvements in endurance performance as a result of caffeine ingestion (15,16). However, the bolus of caffeine used in both these prior studies (15,16) was double (6 mg*kg -1 body mass) than that used in the present study.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The current results also agree with the prior research with younger adults (2) showing enhanced aerobic endurance following caffeine ingestion and research with older adults that has reported improvements in endurance performance as a result of caffeine ingestion (15,16). However, the bolus of caffeine used in both these prior studies (15,16) was double (6 mg*kg -1 body mass) than that used in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, Momsen et al (16) demonstrated that 6mg*kg -1 of caffeine significantly increased maximal walking distance (20%) and maximal isometric knee extension strength (9.8%) in 68 year old patients with moderate intermittent claudication. In agreement with the work of Norager et al (15), endurance was also significantly improved (21.4%), however there was no effect of caffeine supplementation on reaction time and cognition. A later study by Jensen et al (17) adds further ambiguity after reporting that a 6mg*kg -1 caffeine supplement did not significantly improve maximal arm flexion strength and isometric submaximal endurance in subjects aged over 70.…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…Thirty-three peer-reviewed research articles met the inclusion criteria (Alves et al, 1995;Bell, Jacobs, & Zamecnik, 1998;Berglund & Hemmingsson, 1982;Bridge & Jones, 2006;Butts & Crowell, 1985;Cadarette, Levine, Berube, Posner, & Evans, 1983;Cha et al, 2001;Cohen et al, 1996;Collomp et al, 2002;Conway, Orr, & Stannard, 2003;Costill et al, 1978;Denadai & Denadai, 1998;French et al, 1991;Fulco et al, 1994;Graham, Hibbert, & Sathasivam, 1998;Graham & Spriet, 1991;Greer, Hudson, Ross, & Graham, 2001;Ivy et al, 1979;Jenkins, Trilk, Singhal, O'Conner, & Cureton, 2008;Lindinger, Graham, & Spriet, 1993;MacIntosh & Wright, 1995;McLellan, Bell, & Kamimori, 2004;McNaughton et al, 2008;Norager, Jensen, Madsen, & Laurberg, 2005;Pasman et al, 1995;Powers, Byrd, Tulley, & Callendar, 1983;Sasaki et al, 1987;Slivka et al, 2008;Spriet et al, 1992;Trice & Haymes, 1995;Van Soeren & Graham, 1998; Table 3). Three research articles Berglund & Hemmingsson, 1982;Butts & Crowell, 1985) reported Note.…”
Section: Study Characteristics For Caf Versus Placebo Analysismentioning
confidence: 99%